Design, analysis and prototyping of a high speed surface mounted permanent magnet machine - Ng'onga, Maxas (Department of Electrical Engineering, 2019)
Over the recent years, there has been a rise in the demand for high speed and high power density machines for various applications in industry ranging from basic household power tools to the flight controls for aircrafts in the aerospace sector. This has also seen advancements in the power electronics and controls for these machines to deal with the large operating frequencies. The increase in demand for high speed machines has been driven by the industry’s requirement for cost reductions, higher robustness & higher efficiencies. This thesis aims to contribute knowledge to the design and development of a high-speed surface mounted permanent magnet machine. A numerical procedure for the detailed sizing of a high-speed surface mounted permanent magnet (SPM) machine is outlined in this dissertation. An analytical per phase model is formulated to examine the performance parameters of the machine. The analytical model is validated against results obtained from Ansys Electromagnetics Finite Element Analysis (FEA) software. The estimation of core losses in high-speed machines is also of critical importance during electromagnetic design. An immense amount of research has been conducted on the estimation of core losses in machines, however, not much has been done to cover the estimation of highspeed core losses as compared to the traditional low-speed machines. As part of the development of the high-speed machine, the numerical estimation of the highspeed core losses was examined and validation performed using FEA software. On average, there was a difference of about 3-11% between the analytical results and FEA results of the eddy current loss and hysteresis loss. These results demonstrate that the analytical method used to estimate core losses is reasonably accurate when compared to FEA results obtained from ANSYS Maxwell. The prototyping of a high-speed surface mounted permanent magnet machine is investigated. Focus is placed on the major components of the machine whilst highlighting the use of precision machining and the need to maintain high accuracy during manufacturing and assembly of the machine prototype.